Human Resource Management in Improving Employees’ Sharia Financial Literacy of Bank Syariah Indonesia Manado Mantos Branch - Hasan Jan, Radlyah; Makapuas, Jumriati; Ayu Lestari Niu, Fitria (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Objective - This study aims to describe the implementation of Human Resource Management it improving the employees’ sharia financial literacy of Bank Syariah Indonesia Manado Mantos Branch. Design/methodology/approach – Using qualitative methods with data collection through observation, interviews with 4 informants, and documentation. The data analysis includes three stages: data reduction, data presentation, and conclusion. Findings - Employee recruitment planning has not been carried out optimally, the analysis of human resource needs, choice and appointment, and placement of human resources has been carried out well. However, the employees are in the aspect of Well Literate through limited training, regular socialization and sharing sessions such as during briefings, and regular performance assessments and evaluations by leaders. Research limitations/implications – This research was only conducted in one of the branches of Bank Syariah Indonesia in Manado City, Indonesia. Further research can use methods to prove and explain each variable of this study’s findings on the same research object or even a broader one. Practical implications - Improvements and strengthening are needed in recruitment planning, more effective training and socialization, and performance assessments based on sharia competencies. There needs to be a collaboration between internal and external parties of Bank Syariah Indonesia Manado Mantos Branch. Originality/value – This study contributes to examining the intersection of human resource management in Islamic financial institutions. These findings offer valuable insights to improve HRM practices to foster more competent employees in Sharia finance principles, potentially becoming a model for similar institutions.